Approach to Stress Fractures: Report of Three Cases and Review of Literature - Zeynep Tuba Bahtiyarca; Sevil Okan; Sezgi Barlas Şahin; Firuze Ocak (Galenos Yayinevi, 2021)
Stress fractures occur following repetitive and mechanical overloading of the bones. Two known subtypes are fatigue fractures and insufficiency fractures. Generally, pain in the affected bone increases with activity and decreases with rest. They are frequently seen in the tibia, pelvis and foot bones. In the early period, results of direct radiography are generally normal. Diagnosis is based on detailed history assessment, physical examination and advanced imaging methods. Stress fractures are often overlooked and difficult to diagnose; thus, it should be considered in the differential diagnosis if there is clinical suspicion. This report presents three cases of stress fractures in different anatomical regions.